2022
DOI: 10.1155/2022/2785859
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Efficacy and Safety of the Diode Laser (980 nm) and Sclerotherapy in the Treatment of Oral Vascular Malformations

Abstract: Background. Vascular malformations are structural abnormalities which are formed by progressively enlarging aberrant and ecstatic vessels without endothelial cell proliferation and composed of the type of vessel involved, i.e., capillary, veins, and arteriovenous. Treatment of vascular malformations may involve many techniques like sclerotherapy, embolization, surgical resection, cryotherapy, laser treatment, or medical therapy. This observational prospective study is aimed at evaluating and comparing the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a study comparing this sclerosing agent with the diode laser (980 nm), it was found to have significantly fewer side effects when treating the laser group compared to the sclerotherapy group. Both treatment options were considered to be effective for treating vascular lesions, but the authors found the diode laser treatment to be a better option, especially for smaller lesions regarding less postoperative pain and fewer side effects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing this sclerosing agent with the diode laser (980 nm), it was found to have significantly fewer side effects when treating the laser group compared to the sclerotherapy group. Both treatment options were considered to be effective for treating vascular lesions, but the authors found the diode laser treatment to be a better option, especially for smaller lesions regarding less postoperative pain and fewer side effects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis and contracture eventually cause the lesion to disappear [ 7 ]. Because of their safety and efficacy, sodium tetradecyl sulfate (STS), OK-432, monoethanolamine oleate, polidocanol, hypertonic glucose solution, ethanol, sodium morrhuate, bleomycin, and corticosteroids have been used in various oral diseases, including vascular malformation, pyogenic granuloma, mucocele, and ranula [ 7 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is ongoing debate regarding the optimal choice of sclerosing agent and the need for additional interventions alongside sclerotherapy. Several studies have compared the outcomes of interventions with and without sclerotherapy, aiming to determine the efficacy and safety of this treatment modality [ 11 ]. In this review, we examined the results of these studies and explored the benefits and limitations of sclerotherapy compared to other interventions.…”
Section: Reviewmentioning
confidence: 99%